A least squares algorithm for efficient context-based adaptive arithmetic coding - Triantafyllidis, G.A.; Strintzis, M.G. (2001 IEEE International Symposium on Circuits and Systems, 2001)
Discrete wavelet transforms are widely used for lossless image compression, The overall performance of these schemes may be further improved by properly designing efficient entropy coders. A novel technique for the implementation of context-based adaptive arithmetic entropy coding is presented in this paper. This technique is based on the prediction of the value of the current transform coefficient, employing a weighted least squares method, in order to achieve appropriate context selection for arithmetic coding. Experimental results illustrate and evaluate the performance of the proposed technique.